Imaging of Hepatitis B Virus Nucleic Acids: Current Advances and Challenges - Luisa F. Bustamante-Jaramillo; Joshua Fingal; Marie-Lise Blondot; Gustaf E. Rydell; Michael Kann (Viruses, 2022)
Hepatitis B virus infections are the main reason for hepatocellular carcinoma development. Current treatment reduces the viral load but rarely leads to virus elimination. Despite its medical importance, little is known about infection dynamics on the cellular level not at least due to technical obstacles. Regardless of infections leading to extreme viral loads, which may reach 1010 virions per mL serum, hepatitis B viruses are of low abundance and productivity in individual cells. Imaging of the infections in cells is thus a particular challenge especially for cccDNA that exists only in a few copies. The review describes the significance of microscopical approaches on genome and transcript detection for understanding hepatitis B virus infections, implications for understanding treatment outcomes, and recent microscopical approaches, which have not been applied in HBV research.